SPIA Uganda Report 2025: Agricultural Diversity Under Stress - Stevenson, James R. (2025)
This four-page brief highlights and summarizes the key messages, methods, and main results of the extensive and sustained collaboration among the following partners: CGIAR Standing Panel on Impact Assessment (SPIA), World Bank Living Standards Measurement Study team (LSMS), Uganda Bureau of Statistics (UBoS), NARO, MAIFF, and CGIAR researchers. The focus is on six major crops: maize, cassava, banana, beans, sweet potato, and groundnuts.